Strategi Pemberdayaan Muda Menuju Perdamaian Internasional (Studi Kasus : Komunitas YIPC Indonesia) - Fathurohman, Fathurohman; Anwar, Syaifuddin (Jurnal Kajian Stratejik Ketahanan Nasional, 2021)
Pancasila as the nation's personality is an image that must be highlighted in international life. The young generation as the vanguard and the main cluster of a nation must practice the values of Pancasila. Yout Interfaith Peacemaker Community (YIPC) is a collection of youth from different countries and religions, committed to being actively involved in peace building. Youth capacity building through positive work enhancement. This research uses the theory of empowerment of youth, with method of descriptive research based on source of library and interview. The results of the study show that the Youth Response to engage in peace building in each year has increased. The development of social media technology is becoming a positive support for the escalation of movement base. In Indonesia The Base of the Greatest Movement is in the Special Region of Yogyakarta. This preliminary study could serve as a reference for the government in carrying out the Mental Development of the 2020 Agenda of ASEAN.